Effects of the Family Check-Up on reducing growth in conduct problems from toddlerhood through school age: An analysis of moderated mediation - Shelleby, E; Shaw, D; Dishion, T; Wilson, M; Gardner, F (American Psychological Association, 2018)
Objective: The Family Check-Up (FCU) is a preventive intervention found to significantly reduce child conduct problems (CP). This study examined the extent to which parents reported that their child’s CP were a problem for them at baseline (baseline CP) as a moderator of FCU effects into middle childhood and moderated mediation models to explore positive parent-child dyadic interaction and maternal depressive symptoms as mediators. Method: Participants included 731 mother-child dyads followed from child ages 2 to 9.5 (49% female; 28% African American, 50% European American, 13% biracial, and 9% other; 13% self-reported as Hispanic), with half assigned to the FCU. Maternal depressive symptoms, observed parent and child behavior (positive dyadic interaction), and CP were assessed annually. Results: Support was found for baseline CP as a moderator of the FCU, with significant decreases in CP for children in the FCU demonstrating high baseline CP. The following associations did not differ between those with high versus low baseline CP. The FCU significantly increased positive dyadic interaction. Lower maternal depressive symptoms were associated with significantly lower CP. Conclusions: Findings add to existing evidence that preventive interventions are effective for high-risk families, and the FCU is especially beneficial for children whose parents report high levels of CP in early childhood. Further, the FCU significantly improved positive dyadic interaction for families of children with both high and low baseline CP.